Immobilization of phenol-containing molecules on self-assembled monolayers on gold via surface chemistry - Hwang, Hye-Jeong; Choi, Inseong; Kim, Young-Jin; Kim, Young-Kwan; Yeo, Woon-Seok (Colloids and surfaces, B, Biointerfaces, 2019)
[Display omitted] •The Mannich reaction was used to functionalize phenolic molecules permitting their surface immobilization.•The strategy did not compromise the phenol functionality and the biological activity of the immobilized molecules.•The modification and the surface immobilization was confirmed by NMR, XPS, and MALDI-TOF MS.•We showed the immobilized molecules can be functional in an enzyme activity assay. Various phenol-containing molecules such as flavonoids have a wide range of biological effects including anticancer, antimicrobial, and anti-inflammatory properties, and, therefore, they have become subjects of active research for various medicinal and biological applications. To construct applicable materials incorporated with phenol-containing molecules, strategies for immobilization of phenol-containing molecules on solid substrates are required. Although several immobilization methods have been devised and reported, mostly harnessing phenol functionality, however, development of a general immobilization method has been hampered due to its complicated chemical reactions and low reaction yields on surfaces. Furthermore, the use of phenol as a reaction center may compromise the biological activity of phenol-containing molecules. Here, we describe a simple, fast, and reliable method for the surface immobilization of phenol-containing molecules by introducing chemical functional groups, carboxylic acid, thiol, and azide, while maintaining phenol functionality by way of the Mannich-type condensation reaction. We examined the chemical functionalization of naphthol, tyrosine, and flavanone and their immobilization to the self-assembled monolayers on gold via various surface chemistries: the carbodiimide coupling reaction, Michael addition, and the ‘click’ reaction. We strongly believe our method can be a general and practical platform for immobilization of various phenol-containing molecules on surfaces of various materials.